Model administracji rejestrów publicznych. Wybrane zagadnienia: Model administration public records. Selected aspects - Wojciechowski, dr Ryszard (Management and Administration Journal, 2021)
This publication refers to the administration of public records institutions in Poland. The author tries to describe here and refer to various legal sources of public record-keeping by the public administration. Also presents the principles of public record, as the fulfillment of public duties by the administration.